Consciousness of feminism in selected movies among college students - Artuz, Shara Mae F.; Reyes, Rika Jane T.; Villa, Mae Anne F. (2015.)
The study seeks to know the common level of consciousness of feminism in selected films among college students. It anchors on Muzafer Sherif?s Social Judgment Theory that sets responses to stimuli along the latitudes of acceptance, non-commitment and rejection. Parallel to this theory, consciousness of feminism is measured as high level, which means the audiences accept and identify the concept of feminism being present in the films included in this study; medium level, which means the audiences find the concept of feminism objectionable in the films included in this study; and low level, which represents that audience does not accept and identify the concept of feminism being present in the films included in this study. The study employs a survey questionnaire given to 353 students of the University of the Philippines Visayas. Results show that over 73% of the respondents have high consciousness level. It is concluded in this study that majority of the student in the UP Visayas are highly conscious of feminism in feminist-themed films; are conscious of the concept of feminism or can easily identify it in feminist-themed movies.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Conciousness -- Level; Feminism; Feminist themed movies